2021
DOI: 10.1093/icvts/ivab112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between robot-assisted thoracoscopic surgery and video-assisted thoracoscopic surgery for mediastinal and hilar lymph node dissection in lung cancer surgery

Abstract: OBJECTIVES Lymph node dissection (LND) with robot-assisted thoracoscopic surgery (RATS) in lung cancer surgery has not been fully evaluated. The aim of this study was to compare LND surgical results between video-assisted thoracoscopic surgery (VATS) and RATS. METHODS We retrospectively compared perioperative parameters, including the incidence of LND-associated complications (chylothorax, recurrent and/or phrenic nerve paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Other papers however report a conflicting finding. For instance, in a recent article by Haruki et al , the median total LN numbers, though significantly different between RL and VL, were not associated with overall nodal upstaging ( 18 ). The article by Shindo et al mirrors these results in cN0 patients ( 19 ).…”
Section: Discussionmentioning
confidence: 95%
“…Other papers however report a conflicting finding. For instance, in a recent article by Haruki et al , the median total LN numbers, though significantly different between RL and VL, were not associated with overall nodal upstaging ( 18 ). The article by Shindo et al mirrors these results in cN0 patients ( 19 ).…”
Section: Discussionmentioning
confidence: 95%
“…Adequate lymphadenectomy is a milestone in the treatment of NSCLS [ 25 ]. Studies revealed that RATS could achieve more lymph node dissections than VATS [ 26 , 27 ] which indicated that the lymph node dissection of RATS was more thorough.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal upstaging occurred in approximately 20% of our study cohort. The rate of lymph node metastasis in early SCLC was reported as approximately 20%, which is significantly higher than the rate of 10% for early NSCLC [ 13 , 14 ]. It is believed that the higher rate of upstaging in SCLC is due to its aggressive nature.…”
Section: Discussionmentioning
confidence: 99%